Organizational Culture Transformation in Japanese Universities: International Faculty Perspectives on Inclusive Leadership and Diversity Management - Rosie, Rosie (PT. Batari Edu Calya, 2024)
This study explores the dynamics of organizational culture and management practices within a Japanese university from the perspective of international faculty. Employing a qualitative approach, semi-structured interviews were conducted with non-tenured international faculty members to understand their experiences within the context of leadership and diversity management. The findings indicate that the dominant top-down management approach is less effective in promoting inclusivity and the integration of international faculty. The hierarchical organizational culture and a tendency towards uncertainty avoidance emerge as primary obstacles to cross-cultural adaptation and collaboration. This study recommends the implementation of inclusive leadership practices and the development of intercultural competencies to foster a more open and diversity-supportive organizational culture